Comparative Meat Production Performance Evaluation of Buffalo with Cattle at Different Ages - Roy, Biplob Kumer; Haque, Khan Shahidul; Huda, Nazmul (Journal of Buffalo Science, 2017)
An inquisitive on-station feeding trial was carried out to identify the dexterous species and age for beef production with same plane of nutrition. A 2×3 (2 species × 3 ages) factorial experiment was settled for a period of 105 days with eighteen native buffalo and 18 BCB-1 (BLRI Cattle Breed-1) bulls of three age groups (18 months, 24 months and 30 months) and distributed them randomly in six treatment groups having an equal number (6) of animals in each. Intake of nutrients i.e.: DM, CP of buffalo bulls was significantly (p<0.001) higher than BCB-1 bulls in all the cases. The buffalo bulls had significantly higher digestibility of DM (68.0%, p<0.001), OM (67.9%, p<0.001), CP (66.3%, p<0.05), ADF (59.8%, p<0.001) or NDF (59.6%, p<0.001) than cattle (63.0%, 62.7%, 63.6%, 52.4% & 49.6%, respectively). But, the digestibility of DM, OM, CP, ADF or NDF was not affected significantly (p>0.05) by the age of the bulls with any cases. Buffalo bulls gained body weight more rapidly (p<0.001); 1.11 & 0.88 kg/day, respectively and showed a better FCR (p>0.05; 6.72 & 6.86, respectively) than cattle with low feed cost of per kg gain (US 1.62 & US 1.69, respectively). ADG (p<0.01), FCR (p<0.05) and estimated feed cost (p<0.05) affected significantly and increased linearly by the age of bulls, where 18 months bulls of buffalo and BCB-1 performed best. In an aggregation, it revealed that, buffalo performed better than BCB-1 cattle and 18 months age of both species was more responsive for profitable meat production.